ANALISIS PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) PADA LAPORAN KEUANGAN KOPERASI ORIENTASI KEWIRAUSAHAAN CEMERLANG - Ependi, Ependi (AGUSPATI Research Institute, 2021)
This study aims to examine the extent to which accounting standards apply to the preparation of cooperative financial statements, and evaluate their application with theories based on the Public Accountability Accounting Standards for Entities without Public Accountability (SAK ETAP). The research methodology used is descriptive qualitative method because it compares the preparation of financial accounting reports in cooperatives with the theories and provisions contained in SAK ETAP. The data collection technique is primary, in the form of document collection by conducting interviews with the Cemerlang Cooperative in order to obtain more in-depth information about the policies and calculations used as the basis for compiling financial reports. The data analysis technique used is to describe the determination used by cooperatives and SAK ETAP as a guide. The result of the research is that the Cemerlang Cooperative has not fully implemented the provisions contained in SAK ETAP. where Koperasi Cemerlang has not fully complied with the obligations and compliance with the specified taxation. For the treatment of some accounting posts, it is in accordance with SAK ETAP.